Letter from David Robinson to James Curtis Booth - Robinson, David (1861)
David Robinson writes to James Curtis Booth (1810-1888) concerning a potential place as engineer or workman for the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States